2021
DOI: 10.3390/nu13061917
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Kidney Stone Disease

Abstract: The prevalence of kidney stone disease is increasing worldwide. The recurrence rate of urinary stones is estimated to be up to 50%. Nephrolithiasis is associated with increased risk of chronic and end stage kidney disease. Diet composition is considered to play a crucial role in urinary stone formation. There is strong evidence that an inadequate fluid intake is the major dietary risk factor for urolithiasis. While the benefit of high fluid intake has been confirmed, the effect of different beverages, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
102
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(111 citation statements)
references
References 156 publications
(212 reference statements)
0
102
0
9
Order By: Relevance
“…The prevalence of nephrolithiasis was estimated to be 7.2%–7.7% globally and showed an increasing tendency with years, with 5%–10% in Europe, 4% in South America, and 1%–19% in Asia, respectively ( 2 , 3 ). Nephrolithiasis also shows a high recurrence rate of approximately 50% at 10 years ( 4 ). In addition, a graded relation was found between kidney stones and the increasing risk of kidney function loss, even end-stage renal disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of nephrolithiasis was estimated to be 7.2%–7.7% globally and showed an increasing tendency with years, with 5%–10% in Europe, 4% in South America, and 1%–19% in Asia, respectively ( 2 , 3 ). Nephrolithiasis also shows a high recurrence rate of approximately 50% at 10 years ( 4 ). In addition, a graded relation was found between kidney stones and the increasing risk of kidney function loss, even end-stage renal disease ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly crystallizing calcium salts in the kidney are calcium phosphate (CaPi) and calcium oxalate (CaOx) [ 22 ], the latter can form on the basis of UA crystals [ 19 ]. It is thought that high urine pH favours calcium phosphate (CaPi) crystallization, while low or neutral pH promoted precipitation of calcium oxalate (CaOx) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of FR as a causal factor of urolithiasis is still puzzling. On the one hand, epidemiological and clinical studies have shown that FR may be responsible for this disease, while on the other hand consumption of fruits and juices in a diet is still recommended for patients with kidney stones [ 22 ]. To our knowledge, the studies conducted so far have not directly confirmed the relationship between the FR diet and the presence of renal calculi.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney calculus is a common disease worldwide and easily recurs after treatment, which puts heavy burden on the medical and health system. The formation of kidney stones is a multi-factorial process that may involve genetic, metabolic, anatomical and functional abnormalities, and is vitally affected by nutrition ( 1 ). A variety of foods or diets are related to kidney stones, such as fruit juices and fruit juice beverages, soft drinks, tea, coffee ( 1 ), and the Mediterranean diet ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of kidney stones is a multi-factorial process that may involve genetic, metabolic, anatomical and functional abnormalities, and is vitally affected by nutrition ( 1 ). A variety of foods or diets are related to kidney stones, such as fruit juices and fruit juice beverages, soft drinks, tea, coffee ( 1 ), and the Mediterranean diet ( 2 ). Many nutrient components are also associated with kidney calculi, including protein, fat, and carbohydrates ( 1 ).…”
Section: Introductionmentioning
confidence: 99%